Effect of alkali treatment on mechanical properties of the green composites reinforced with milkweed fibers. Issue 1 (2nd January 2018) - Sayanjali Jasbi, Moghgan; Hasani, Hossein; Zadhoush, Ali; Safi, Somayeh
Abstract: Polymeric composites disadvantages in terms of high price and non-recoverability make them unsuitable for some applications. Otherwise, natural fibers would be degraded easily and their prices are much lower as compared with most of the commonly used synthetic fibers, especially in composite manufacturing. Hollow Milkweed fiber with non-crimped nature is a known natural fiber which could have high potential to be used as composites reinforcements due to its low-density property. Increasing demand for natural fiber-reinforced composites as well as unique characteristics of Milkweed fibers reveal the need to study the mechanical properties of such fiber-reinforced composites. In this study, milkweed fibers were initially fed to laboratory carding machine in order to be formed as a nonwoven layer which was then applied to a low-velocity needle-punching operation. Surface modifications were carried out on the needle-punched nonwovens using 5% NaOH at 50–60 °C and three different treating time levels (30, 60 and 90 min). The produced nonwovens were then treated in a mixture of boiling water and detergent for 1 h. For making composite parts, the modified nonwovens were impregnated in Ploy vinyl acetate (PVAc) resin using the hand-layup method. The alkali treatment effects regarding the process time period on mechanical properties of the natural-reinforced composites were investigated. The findings suggested significant affectability of the composites mechanical properties by varying the time of alkali treatment, NaOH concentration as well as the type of surface modification process which are all mainly resulted in improving the interaction between fibers and matrix phase.